Application of fourth industrial revolution technologies to ventilation design and environmental monitoring criteria for platinum mining in Zimbabwe - Chikande, Tonderai (My University, 2022)
Mine ventilation plays a pivotal role in underground mining operations. It is required to dilute and remove dust, gases, diesel contaminants and to remove heat thereby creating a thermally acceptable, conducive working environment. Most platinum mines on the Great Dyke of Zimbabwe are highly mechanised as they utilize trackless diesel equipment during the extraction process. The fourth industrial revolution was introduced to enhance productivity, safety, reduce costs, operational longevity and to monitor all processes in real time. The internet of things (IoT) together with other digital revolution techniques were then investigated and implemented in the mining industry for process optimisation and data analytics. The Great Dyke of Zimbabwe faces several challenges from fluctuating metal prices, safety concerns, productivity optimisation and a continuously transforming competitive landscape. Underground mining operations present a technically challenging and hazardous environment for workers, through inadequate ventilation, exposure to dust, heat and gas as well as threat of rock falls or mine collapse. Recent studies demonstrated that in highly mechanized platinum mines, primary ventilation systems account for 40-60% of the mines’ energy consumption hence cognizance of this must be taken during mine design. The primary reason for this considerable expense is that most underground ventilation systems are designed for the peak demand regardless of the actual demand, which is commonly dictated by diesel equipment usage. The ever-increasing geological complexities, higher degree of mechanization and the espousal of more stringent health regulations have generally influenced more air demands in underground operations. Such increases in air quantity result in augmented energy consumption due to the cubic relationship of quantity and power. As a result, to mitigate prohibitive ventilation costs, underground mines must optimise their ventilation systems during their design and must explore cost cutting initiatives through digital transformation technologies. The adoption of electric vehicles, autonomous vehicles and ventilation on demand systems may be implemented in room and pillar platinum mines to reduce operating costs and to enhance safety and productivity. Most platinum mines on the Great Dyke tend to operate their ventilation systems at peak level, despite the mine’s air volume being well in excess of the “true” ventilation needs, due to a lack of appropriate ventilation controls. In this research, ventilation on demand system in a bord and pillar platinum mine was designed and installed to minimize the redundant use of air in underground operations. Fourth industrial revolution techniques were applied to environmental monitoring systems thereby optimizing airflow demands. The mine managed to reduce its annual power consumption by 23% through the implementation of manual control and time of day scheduling levels of the ventilation on demand concept. There was also a 6% productivity improvement mainly attributable to a significant reduction in the re-entry period. This thesis introduces a novel concept of ventilation optimisation through digital transformation in room and pillar platinum mines. A system was designed, installed and commissioned though there is currently an ongoing optimisation process to harness the full benefits of ventilation on demand (VOD). In a large mechanised operation, if a mine can reduce airflow through eliminating redundant air supply, the resultant power consumption or cost will be reduced due to the cubic relationship of speed and power. The ventilation on demand concept had not been rolled out to any bord and pillar mining operation before 2016 due to the nature of mining operations. Efficient air distribution in bord and pillar platinum mines will be achieved through the integration of internet of things with empirical techniques extracted from real-time data. The ventilation system is adjusted in real time to meet the triggered ventilation demand based on the activities undertaken. This thesis describes various options to optimise and apply the concept to hard rock bord and pillar platinum mines operating on the Great Dyke of Zimbabwe. The increased power demand from ventilation systems necessitated the need to optimize the amount of air sent underground through the application of fourth industrial revolution techniques. The ventilation on demand systems coupled with advanced control processes modulate the airflow of main surface fans and auxiliary fans thereby optimizing mines ventilation systems.
A thesis submitted in fulfilment of the requirements for the degree of Doctor of Philosophy in Engineering to the Faculty of Engineering and the Built Environment, School of Mining Engineering University of the Witwatersrand, Johannesburg, 2022